2011
DOI: 10.1177/0748233711422726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal clothianidin exposure on behavioral development in F1 generation mice

Abstract: Female mice were exposed maternally to clothianidin through diet at levels of 0% (control), 0.002%, 0.006%, and 0.018% during gestation and lactation periods. Selected reproductive and neurobehavioral parameters were measured in F₁ generation. There was no adverse effect of clothianidin on litter size, litter weight, or sex ratio at birth. The average body weight of male and female offspring was increased significantly in a dose-related manner during the lactation period. With respect to behavioral development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
2
39
1
Order By: Relevance
“…Although it has no teratogenic and developmental effects on fetuses at NOAEL doses, however, fetal death, decrease in fetal weight or ossifying delay in sternebrae have been reported (Sumitomo Chemical Takeda Agro Company, Ltd 2003). Tanaka (2012) have reported that CTD exposure causes some neurobehavioral effects without litter size, litter weight or sex ratio in mice during developmental period. Based Data are presented as mean ± SEM values.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although it has no teratogenic and developmental effects on fetuses at NOAEL doses, however, fetal death, decrease in fetal weight or ossifying delay in sternebrae have been reported (Sumitomo Chemical Takeda Agro Company, Ltd 2003). Tanaka (2012) have reported that CTD exposure causes some neurobehavioral effects without litter size, litter weight or sex ratio in mice during developmental period. Based Data are presented as mean ± SEM values.…”
Section: Discussionmentioning
confidence: 98%
“…The concentration of CTD in the tissues and organs declines rapidly, and therefore it does not accumulate in the tissues and organs including testis (Yokota et al 2003). Tanaka (2012) have reported that CTD administration through diet to female mice during the gestation period has no effect on selected reproductive parameters including litter size, litter weight, or sex ratio at birth. However, Najafi et al (2010) have alleged that the neonicotinoid, imidacloprid, administration to rats daily for 60 days leads to significant reproductive disorders including a histological adverse effect on testicular tissue, spermatogenesis, sperm viability, velocity and abnormality.…”
Section: Introductionmentioning
confidence: 97%
“…However, increasing evidence to the contrary [11,12,13,14,15,16,17,18,19], and consideration of some neonicotinoid metabolites showing high affinities for mammalian nAChRs [3], suggests that neonicotinoids have potential developmental neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the neonicotinoids thiamethoxam and clothianidin induced dopamine release in the rat striatum via nAChRs [12] and thiamethoxam altered behavioral and biochemical processes related to the cholinergic systems in rat [13]. Gestational administration of clothianidin induces behavioral disorders in F1 mice [14] and exposure to clothianidin and other stress causes behavioral and reproductive abnormalities in male mice [15]. Exposure to IMI alters learning performance and related gene expression in infant and adult rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…There are very limited reports related to effects of the neonicotinoids, especially CTD, on male reproduction. For example; Tanaka (2012) has reported that CTD administration through diet to female mice during the gestation period has no effect on selected reproductive parameters, including litter size, litter weight, or sex ratio at birth. However, in our previous study (Bal et al, 2012a), we demonstrated that CTD exposure at the no observed adverse effect level (NOAEL) dose (32 mg/kg) daily for 90 days caused significant decreases in reproductive organ weights, sperm concentration, testicular GSH level, and significant increases in some testicular fatty acid composition, cholesterol level, apoptotic germ cells, and sperm DNA fragmentation in developing male rats.…”
Section: Clothianidinmentioning
confidence: 98%